School-based health education effect on knowledge, attitude, and practices of dengue prevention among school children: a systematic review - Rahmat Dapari; Abdul Qayyum Jumidey; Rosliza Abdul Manaf; Mohd ‘Ammar Ihsan Ahmad Zamzuri; Mohd Rohaizat Hassan; Nazri Che Dom; Syed Sharizman Syed Abdul Rahim (Springer Nature Switzerland AG, 2025)
Introduction Dengue is a mosquito-borne viral disease caused by dengue virus. The incidence of dengue has been steadily increasing globally in recent decades. The main treatment modality focuses on symptomatic relief. Primary prevention such as vector control and community education remain the mainstay of dengue control. School-based health education is one of the commonly applied interventions among school-age children to improve dengue control. Objective This systematic review aimed to systematically analyse and determine the impact of various school-based health education programmes on the knowledge, attitudes, and practices of dengue prevention among school children. Methods Articles related to school-based health education with dengue prevention were retrieved electronically from three diferent databases (EBSCOhost-Medline, Scopus, and Pubmed). Articles were screened by independent reviewers. Selected articles based on the inclusion and exclusion criteria were stored in Microsoft Excel. All included articles were critically appraised to assess the quality of the studies using the Mixed Method Appraisal Tool (MMAT). Results Of the 582 articles identifed, nine were included in the fnal review. Overall, there was an increase in knowledge, attitude, and practice regarding dengue following school-based health education. However, knowledge appeared to be the most signifcant variable as all studies showed a signifcant increase in knowledge. Hence, educational interventions exerted a more prominent impact on the knowledge of dengue infection compared to attitude and practices among school children. Conclusion Further research is warranted to establish stronger evidence and evaluate the long-term impact of these interventions on students’ knowledge, attitudes, and practice.